Upaya Pendekatan Kepemimpinan dan Model Kepemimpinan Kepala MI Ma'arif Kemangguan - Kuni Fajriyah; Titik Fajriyati (LPPM IAINU Kebumen, 2022)
This journal discusses the leadership approach and leadership model applied by the Head of Madrasah MI Ma'arif Kemangguan. The purpose of this study is to determine the leadership approach and leadership model that is carried out and applied by the Head of Madrasah MI Ma'arif Kemangguan. This research was conducted in order to determine the leadership approach taken by the head of the Madrasah MI Ma'arif Kemangguan in carrying out his duties as a leader. In addition, this study also examines the leadership model carried out by the Head of Madrasah MI Kemangguan. In this study, the author uses a qualitative method, by conducting interviews with informants. The main resource person in this study was the Head of Madrasah MI Ma'arif Kemangguan. In addition, as information or supporting data in this study, namely conducting research on two teacher boards of MI Ma'arif Kemangguan and one student guardian of MI Ma'arif Kemangguan. The result of the research is to know the leadership approach and leadership model that is carried out by the Head of Madrasah MI Ma'arif Kemangguan. The leadership approach taken by the Head of Madrasah MI Ma'arif Kemangguan is by using a situational approach, namely the pattern of behavior shown by a leader when leading and able to influence the activities of others, both as individuals and groups. While the leadership model carried out by the Madrasah Head of MI Ma'arif Kemangguan is a participatory leadership model in which the leader holds little control in the decision-making process, here the leader only describes the problem which is then discussed together with his subordinates.